HIKAYAT MARTALAYA: BUDAYA LOKAL, AGAMA, DAN AKULTURASI DI PALEMBANG: HIKAYAT MARTALAYA: LOCAL CULTURE, RELIGION, AND ACCULTURATION IN PALEMBANG - Mahmudah Nur (Balai Penelitian dan Pengembangan Agama Jakarta, 2014)
Palembang is one of the most important areas for the development of Malay literature. The features of Malay literature in Palembang are of great variety compared to those developed in other areas. This article examines Hikayat Martalaya (Tale of Martalaya), a Malay literary work written by Sultan Mahmud Badaruddin II of Palembang. The manuscript is a collection of the National Library of the Republic of Indonesia (code MI 005). Using an inter- textual approach, the author of this article analyzes the manuscript from the perspective of literary sociology. The manuscript uses many Javanese words in describing the historical origins of Palembang. The author argues that the manuscript clearly shows the process of acculturation in which local culture and religion meet. Although not saliently narrated, the Islamic elements in the manuscript obviously relate to the process of Islamization taking place in Palembang, while the Javanese elements are found in their relations with the legitimacy of the rule of the king who established good relationship with the kingdom of Majapahit and Demak in Java. The influences of other languages, such as Persian and Indian, are also obvious. Key Words: Hikayat Martalaya, local culture, religion, acculturation. Palembang merupakan salah satu wilayah yang sangat penting bagi perkembangan kesusasteraan Melayu. Corak kesusasteraan di Palembang lebih beraneka ragam dibandingkan dengan kesusasteraan Melayu di daerah lainnya, sebagaimana yang terlihat pada teks Hikayat Martalaya karangan Sultan Mahmud Badaruddin II. Asal usul Palembang diceritakan dengan banyak menggunakan kata-kata Jawa. Data penelitian ini adalah naskah Hikayat Martalaya (Kode Ml 005) koleksi Perpustakaan Nasional Republik Indonesia (PNRI) di Jakarta, dan dianalisis dengan pendekatan intertekstual dan sosiologi sastra. Penelitian ini menunjukkan, bahwa proses akulturasi antara budaya lokal dan agama di Palembang tergambar jelas melalui teks-teks dalam naskah tersebut. Walaupun unsur Islam tidak mendominasi, namun mempunyai kaitan yang sangat erat dengan proses Islamisasi. Adapun unsur Jawa dalam teks ini berkaitan dengan legitimasi kekuasaan raja yang melakukan hubungan baik dengan kerajaan besar di Jawa, seperti Majapahit dan Demak. Beberapa pengaruh bahasa lain seperti Persia dan India terlihat jelas. Kata Kunci: Hikayat Martalaya, akulturasi, budaya lokal, agama.